Effects of nigella sativa (Linn.) seeds extract treatment on the hippocampal MAP2 and GFAP mRNA expressions in the experimental neurodegeneration - Azzubaidi, Marwan Saad; Babar, Z.M.; Saxena, Anil Kumar; Talib, Norlelawati A. (Wiley, 2014)
Background: Experimental neurodegeneration can be induced by two vessel occlusion intervention (2VO). Nigella sativa (Linn.) seeds extract (NSSE) has recently shown to enhance memory and learning task performances in rats with 2VO. Prevention of neuroinﬂammation and/or of toxic free radical formation are possible mechanisms. The glial ﬁbrillary acidic protein (GFAP) is a vital neuroinﬂammatory marker in neuroscience researches. GFAP was found to be up-regulated in 2VO rats indicating astrogliosis. Microtubule associated protein type II (MAP2) is an important marker for neuroprotection during and after ischemic brain injury or hypoxia. It was found to be down-regulated in 2VO rats. Aim: The current study aimed to compare the hippocampal MAP-2 and GFAP mRNA expressions of 2VO (untreated) male rats in the experimental neurodegeneration with other groups of healthy control and NSSE treated rats. Method: 18 adult male Sprague Dawley rats were randomly divided into 3 groups (n = 6); Healthy Control (HC); 2VO- without treatment (2VO); 2VO + NSSE-treated (NSSE). The NSSE group was pre-treated (2 ml/kg/day, orally) for 10 days prior to 2VO surgery and continued until all animals were sacriﬁced at the end of 10th postoperative week. Hippocampal samples were then collected; total RNA was extracted, puriﬁed and relatively quantiﬁed via reverse transcribed cDNAasperΔΔCq of RT-qPCR assay. Results: There was a signiﬁcant 3 folds difference of GFAP mRNA expression in both HC and NSSE groups as compared to that of 2VO. However, GFAP mRNA expression difference was not signiﬁcant (P = 0.52) of for NSSE vs. HC. Hippocampal MAP2 mRNA expression of NSSE group appeared to be insigniﬁcantly different from the untreated 2VO group. Conclusion: Prolonged treatment with NSSE has the potential to prevent hypoperfusion-induced neuroinﬂammation within the hippocampus. This may be a potential mechanism for neuroprotection against mild cerebral ischemic injuries. However, NSSE was unable to prevent loss of neuronal plasticity.